Present and perspectives of classical technique in cross country skiing - Nosek, M. (Journal of Outdoor Activities, 2012)
In the last few years has been observed a progression of riding techniques in the cross-country skiing race, which cause to speeding up this kind of skiing. Technical changes are recorded especially for the classic cross-country skiing techniques, specifically for double poling. The article surveys the history and current status of classical techniques, it describes the significant researches which are dealing with progression of double poling and it`s trying to forecast future developments at the same time. The result is an ascertainment that prestige of double poling is growing and with a development of training and increasing speed of run will grow also its share in overall usage of race track.